Reconciling the new keynesian model with observed persistence - Kenneth Leong (Bank of Finland, 2002)
Despite sound theoretical foundations, a drawback of the New Keynesian model is its inability to generate adequate persistence in the variables it seeks to explain.A common solution is to modify the model to include lagged variables.However, this is unsatisfactory, as many such modifications depart from the microeconomic underpinnings of the original model.This paper presents results from simulation exercises that support the fully forward-looking New Keynesian model.In particular, we show that the exchange rate channel of monetary policy, which has been largely overlooked in existing studies of persistence, is instrumental in generating inflation persistence.However, the combination of full forward-looking behaviour and an open economy is unable to generate sufficient persistence in the output gap. Adding an autocorrelated noise term to the assumption of rational expectations makes the model capable of generating persistence matching that of US inflation, the output gap, and the nominal interest rate, as well as the real exchange rate.
URN:NBN:fi:bof-20140807557
Keywords: E31; E52; 330; New Keynesian model; rational expectations; persistence; open economy